Analysis of Labor Productivity Factors in the Inspection Division (Case Study at PT. XYZ) - Hafid Zuhdi Kharisma Putra; Hana Catur Wahyuni (Universitas Muhammadiyah Sidoarjo, 2019)
The purpose of this study is to find out data/factors that cause lack of productivity; knowing the model of the relationship and the influence of accuracy, compensation, leadership, and the environment on emplooye productivity; and to find out the design/solution to increase the productivity of inspectors. The method used in completing this research is the Partial Least Square (PLS) method. From the result of the research that has been done it is known that Accuracy (X1); Leadership (X3); and Work Environment (X4) significantly influence Productivity (Y1) except Compensation (X2). And the most influential variable Productivity (Y1) is Leadership (X3) with percentage of 50,4% and the lowest is Accuracy(X1) with a percentage of 20,1%.